Information Seeking Behavior Among Final Year Students at National Teachers' College Kabale. - Nduhukire, Bonus (Kabale University, 2023)
This research report investigated the information needs and seeking behavior of final-year students of the National Teacher's college Kabale, for consecutive three academic sessions. A questionnaire instrument was designed and administered to final-year students in three programs that is DEP year three DES final year DECE final year CEC final year. The sample sizes of respondents were 120 selected within and across the four above academic programs at National Teachers' College Kabale using a stratified sampling technique with a questionnaire representing 98% were returned in a usable form. The findings show that final-year students' need for course-related information was highest in each of the programs studied. The use of consultations from lecturers references through the Librarian was the common strategy for seeking information while the purpose for information varied over the years -from examination, and self-development to selecting a project topic (long essay). The study concluded that the information needs and seeking behavior of students depend on the year and course (school) of study. Improvement on the staff-student relationship and information search strategy was highly recommended.